Investigation of Corneal Astigmatism in Chinese Patients With Primary Angle Closure Disease. Issue 12 (December 2018) - Zuo, Chengguo; Gong, Ruowen; Chen, Weirong; Chen, Chuyin; Su, Jinai; Wei, Kun; Gao, Xinbo; Lin, Mingkai; Ge, Jian
Abstract : Purpose: The purpose of this study was to analyze the demographics and distribution of corneal astigmatism before lens extraction in patients with primary angle closure disease (PACD). Methods: Preoperative partial coherence interferometry was performed in patients with PACD. The demographic and biometric data, including corneal astigmatism and keratometry (K), were recorded. Results: The study comprised 808 cases (1001 eyes) with a mean age of 67.66±9.07 years, and the mean axial length was 22.55±0.89 mm. The mean corneal astigmatism was 1.08±0.78 diopter (D). Corneal astigmatism was between 0.25 D and 1.25 D in 66.50% of the eyes, 1.25 D or higher in 29.68% of the eyes and <0.25 D in 3.82% of the eyes. The corneal astigmatism of primary angle closure suspect (PACS), primary angle closure (PAC) and primary angle closure glaucoma (PACG) were 1.08±0.77 D, 0.98±0.62 D, and 0.89±0.69 D, respectively. In total, 50.60% of the eyes were classified as astigmatism against the rule (ATR), 28.69% of the eyes were with the rule, and 20.71% of the eyes were oblique. ATR astigmatism increased significantly with age ( P <0.001). After matching, corneal astigmatism of PACD was 1.07±0.77 D, although it was statistically significantly higher than that of ARC (0.98±0.66 D, P =0.018), the 2 demonstrated no clinical difference. Conclusions: The results provide normative data of corneal astigmatism for PACD patients. Corneal astigmatism was mainly distributed between 0.25 D and 1.25 D. The findings largely concur with published results in age-related cataract subjects.